A PAK1 mutational hotspot within the regulatory CRIPaK domain is associated with severe neurodevelopmental disorders in children - Scorrano, Giovanna; D'Onofrio, Gianluca; Accogli, Andrea; Severino, Mariasavina; Buchert, Rebecca; Kotzaeridou, Urania; Iapadre, Giulia; Farello, Giovanni; Iacomino, Michele; Dono, Fedele; Di Francesco, Ludovica; Fiorile, Maria Francesca; et al. (Pediatric neurology, 2023)
Background - P-21-activated kinases (PAKs) are protein serine/threonine kinases, part of the RAS/mitogen-activated protein kinase pathway. PAK1 is highly expressed in the central nervous system and crucially involved in neuronal migration and brain developmental processes. Recently, de novo heterozygous missense variants in PAK1 have been identified as an ultrarare cause of pediatric neurodevelopmental disorders. - Methods - We report a series of children affected with postnatal macrocephaly, neurodevelopmental impairment, and drug-resistant epilepsy. Repeated electroencephalographic (EEG) and video-EEG evaluations were performed over a two- to 10-year period during follow-up to delineate electroclinical histories. Genetic sequencing studies and computational evaluation of the identified variants were performed in our patient cohort. - Results - We identified by whole-exome sequencing three novel de novo variants in PAK1 (NM_001128620: c.427A>G, p.Met143Val; c.428T>C, p.Met143Thr; c.428T>A, p.Met143Lys) as the underlying cause of the disease in our families. The three variants affected the same highly conserved Met143 residue within the cysteine-rich inhibitor of PAK1 (CRIPaK) domain, which was identified before as a PAK1 inhibitor target. Computational studies suggested a defective autoinhibition presumably due to impaired PAK1 autoregulation as a result of the recurrent substitution. - Conclusions - We delineated the electroclinical phenotypes of PAK1-related neurological disorders and highlight a novel mutational hotspot that may involve defective autoinhibition of the PAK1 protein. The three novel variants affecting the same hotspot residue within the CRIPaK domain highlight potentially impaired PAK1-CRIPaK interaction as a novel disease mechanism. These findings shed light on possible future treatments targeted at the CRIPaK domain, to modulate PAK1 activity and function.
Online verfügbar 16 September 2023, Version des Artikels 10 October 2023
Gesehen am 12.04.2024